Experimental allergic encephalomyelitis: peculiarities of pain-relieving therapy and place of anticonvulsants as analgetics - Nefyodov O.O.; MamchurV.I. (Medičnì Perspektivi)
Multiple sclerosis (MS) is the most common demyelinating disease affecting mainly young people of the working age (16-45 years) and quickly leading to disability. Available data constitute that up to 80% of MS patients suffer from pain at different disease periods. Pain management and the analgesic drug choice in MS patients may be difficult. Anticonvulsant drugs possess an analgesic activity and are widely used in patients presenting painful neuropathic symptoms. Based on that, we aimed to investigate the nociceptive potential changes as well as the research-oriented behavior using the "open field" test in rat. An experimental animal equivalent of multiple sclerosis has been modeled, based on the methylprednisolone (M) administration. Animals were also administered anticonvulsants (carbamazepine, topiramate, sodium volproat, pregabalin and gabapentin). The study showed advantages of gabapentin and pregabalin use in simulated disease treatment. This statement is based on the "open field" test results, where the motor-oriented rats’ behavior was evaluated. Administration of M+gabapentin and M+pregabalin showed positive dynamics of the motor activity: the number of squares crossed increased by 80.86% (p<0.05) and 81.73% (р<0.05) respectively. Maximum recovery of the research activity (peeking in "mink") was registered in animals administered M+pregabalin: the increase rate was 300% (r<0.05) comparing with the 12th day of experiment. It was shown, that 5-days administration of M+gabapentin and M+pregabalin caused muscle tone improvement by 190% (p<0.05) and 200% (p<0.05) respectively, comparing with animals with untreated multiple sclerosis. A significant increase of analgesic activity of M+pregabalin and M+gabapentin combinations used together with methylprednisolone by 4.1 (p<0.05) and 3.6 (p<0.05) times was registered comparing with the initial methylprednisolone background.